Religious Involvement and Telomere Length in Women Family Caregivers. Issue 1 (January 2016) - Koenig, Harold G.; Nelson, Bruce; Shaw, Sally F.; Saxena, Salil; Cohen, Harvey Jay
Abstract : Abstract: Telomere length (TL) is an indicator of cellular aging associated with longevity and psychosocial stress. We examine here the relationship between religious involvement and TL in 251 stressed female family caregivers recruited into a 2-site study. Religious involvement, perceived stress, caregiver burden, depressive symptoms, and social support were measured and correlated with TL in whole blood leukocytes. Results indicated a U-shaped relationship between religiosity and TL. Those scoring in the lowest 10% on religiosity tended to have the longest telomeres (5743 bp ± 367 vs. 5595 ± 383, p = 0.069). However, among the 90% of caregivers who were at least somewhat religious, religiosity was significantly and positively related to TL after controlling for covariates ( B = 1.74, SE = 0.82, p = 0.034). Whereas nonreligious caregivers have relatively long telomeres, we found a positive relationship between religiosity and TL among those who are at least somewhat religious.